(untitled) (World Bulletin of Social Sciences, 2026)
This article explores the scientific, theoretical, and pedagogical significance of using maqom rhythmic cycles (usul) in solfeggio instruction. It examines the contradictions between the traditional European tonal-harmonic solfeggio system and the modal-monodic nature of Uzbek maqom music. Special attention is given to the role of rhythm as a fundamental component of musical thinking, encompassing temporal units, meter, rhythmic formulas, and tempo. Drawing on B. Teplov’s psychological theory of musical abilities, the study emphasizes the central role of rhythmic perception in musical cognition. The article substantiates the importance of maqom rhythmic structures in developing internal metrical sense, modal awareness, auditory memory, performance skills, and national musical thinking. Furthermore, it reveals the methodological potential of integrating usul, iyqo’ (rhythmic motion), sequence, and the interaction of stable and unstable tones into the solfeggio curriculum. The research is grounded in the theoretical concepts of S. Matyakubova’s maqom solfeggio methodology.